The Effect of Socio-Economic Changes in the Community on the Value and Face of Traditional Village Houses (Case Study: Tenganan Village, Karangasem Regency, Bali Province) - Verza Dillano Gharata; Widi Dwi Satria; Maqbul Kamaruddin (Universitas Bandar Lampung (UBL), 2022)
Tenganan Pegringsingan Village is located in the east of the island of Bali, especially in the Manggis District, Karangasem Regency. The Tenganan Pegringsingan Traditional Village is included in one of the